Standard EVAR in large necks - is it a reasonable solution? - Oliveira-Pinto,José (2019)
Introduction: Endovascular aneurysm repair (EVAR) has expanded into progressively more challenging anatomies. Proximal neck-morphology represents the major determinant of EVAR durability. Neck-diameter constitutes one of the most important anatomical neck features and influence proximal sealing over time. The purpose of this study is to investigate the influence of wide proximal necks on outcome after standard EVAR. Methods: MEDLINE databases were searched to identify publications addressing the relation between aortic neck diameter and incidence of AAA-related complications. Results: Six studies were included in our review, addressing 6602 patients: 1616 with large necks and 4986 with small necks. Five studies, including 6446 patients, reported higher rates of type 1A endoleak in patients with large necks with hazard/odds ratios ranging between 2.3-4.1. One study found a higher risk of post-implant rupture in patients with necks>30mm (HR: 5.1; 95% CI, 1.4-19.2). Four studies reported on the influence of wide necks on AAA-related mortality without finding any association. Reduced overall survival was seen in patients with large necks in 4 studies (long term survival ranged between 61.6 and 68% for wide neck patients and 75-90 % for small neck patients), mostly attributable to cardiovascular causes. Conclusions: Patients with wide proximal necks are at greater risk for type 1A endoleak, post-implant rupture and overall-mortality. This subgroup of patients may be considered for more complex proximal seal strategies with fenestrated/branched devices or open repair, although there is no evidence of superiority of alternative strategies to standard EVAR in large necks. This subgroup should be offered more stringent imaging follow-up and aggressive treatment of medical comorbidities.